STUDI GENETIK SIFAT MANIS JAGUNG (Zea mays L.) Genetic Study on Sweetness of Sweet Corn (Zea mays L.) - Wahyuni, Endang Sri; Hartatik, Sri; -, Hartana (Pendidikan Biologi,Universitas Islam Jember, 2014)
An experiment to study the inheritance of sweetness in sweet corn has been conducted since May to October 2004 in Arjasa, Jember region and at Seed Technology Laboratory of Agricultural Faculty – University of Jember. Randomized Complete Block Design with sub-sample was used in this study and four replicates. The result showed that genotypes had significantly different on all observed parameters and sugar content heritability value is 20.33%. The gene that determines sweetness had a linkage with wrinkled seed type character. Self-fertilization of sweet corn produced 100% wrinkled seeds. It indicated that wrinkled seed was controlled by recessive homozygous gene. On the other hand, self-fertilization of smooth seed produced two ear types, the first type was 100% smooth seed, which meant that it was controlled by dominance homozygous gene; the other produced smooth seed and wrinkled seed by 3:1 ratio, indicated that it was controlled by heterozygous gene. Key words: sweet corn, sweetness, heritability.